Analysis of factors affecting the construction duration of public health emergency medical facilities - Zhao, Wenchao; He, Haibo (Frontiers in Public Health, 2023)
Objectives: This study explores factors influencing the construction duration of public health emergency medical facilities and the path to enhance them to provide enlightenment for improving the level of public health emergency medical facility construction. Methods: Combining 30 relevant emergency medical facility construction cases in different cities in China from 2020 to 2021, 7 condition variables and an outcome variable were selected, and necessary and sufficient condition analyses of duration influence factors were conducted using the fsQCA method. Results: The consistency of 7 condition variables was less than 0.9, which shows that the construction period of public health emergency medical facilities is not independently affected by a single condition variable but by multiple influencing factors. The solution consistency value of the path configurations was 0.905, indicating that 4 path configurations were sufficient conditions for the outcome variables. The solution coverage of the 4 path configurations was 0.637, indicating that these 4 path configurations covered approximately 63.7% of the public health emergency medical facility cases. Conclusion: In order to shorten the construction duration, the construction of emergency medical facilities should focus on planning and design, choosing an appropriate form of construction, reasonably deploying resources, and vigorously adopting information technology.